Resveratrol induces apoptosis of benign prostatic hyperplasia epithelial cell line (BPH-1) through p38 MAPK-FOXO3a pathway - Chao Li; Wan-Li Hu; Meng-Xin Lu; Guan-Fa Xiao (BMC, 2019)
Abstract Background Resveratrol is reported to inhibit the growth of prostate, which is characteristic of benign prostatic hyperplasia (BPH) condition. However, the mechanism remains unclear. This study aimed to identify the effects and probable mechanism of resveratrol on BPH. Methods We used the BPH epithelial cell line BPH-1 to investigate the effect of resveratrol. Cells were treated with various concentrations of resveratrol, and its effects on cells viability, apoptosis, ROS accumulation, and cell cycle were assessed. Western blot was used to examine activation of p38 MAPK and protein levels of FOXO3a, Bcl2, Bcl-XL, and caspase3. Cells were also co-treated with the p38 MAPK inhibitor SB203580 or ROS scavenger N-Acetyl-L-cysteine (NAC) to further investigate the mechanism. Results Resveratrol treatment inhibited the growth of BPH-1 and increased apoptosis of cells. In addition, levels of phosphorylated p38 MAPK level was elevated and FOXO3a repression was observed. Concomitantly, ROS was accumulated. All of these resveratrol-mediated effects were suppressed by additional treatment with SB203580 or NAC. Resveratrol was also found to induce cell cycle arrest at S phase. Conclusions Resveratrol can activate p38 MAPK and repress FOXO3a, thereby causing repression of SOD2, catalase, and increase of ROS accumulation, leading to apoptosis in BPH-1 cells.